Measuring of Plasma Melatonin Level in Patients with Preeclampsia - Shalal, Maad M.; Kadhim, Ishraq M.; Abbas, Nada S.; Abdulsattar, Ghaidaa (Journal of the Faculty of Medicine Baghdad, 2017)
Background: disturbed physiological rhythm of blood pressure in preeclampsia is a common finding. The role of oxidative stress in pathogenesis of preeclampsia is well accepted. Melatonin is a powerful free radical scavenger so it’s rapidly consumed by enhanced reactive oxygen species in preeclampsia causing non-dipping in blood pressure. Objective: To evaluate the change in plasma melatonin levels in patients with preeclampsia and its relationship with blood pressure. Patients and methods: In this prospective case control study a total of 40 primigravidae pregnant women were recruited during the period of 11 months between August 2015 and August 2016 in Baghdad teaching hospital, medical city, Iraq, divided into two groups: First groups: (cases group) were 20 primigravidae pregnant women with PE. Second group: (control group) were 20 normal healthy primigravidae. Blood Pressure measurement, melatonin blood samples were taken, plasma melatonin levels measurement was done by ELISA immunoassay. Urine was collected over 24 hours for protein in urine measurement. Results : Plasma Melatonin level in control , day and night was (22.72 ± 2.6 pg/mL ) , (75.26 ± 2.99 pg/mL ) compared to Plasma Melatonin level in dipper PE day and night (20.5±2.4 pg/mL ) , (75.26 ± 1.8 pg/mL) which was statistically not significant( P value 0.055 ) , (P value 1.0) respectively . Plasma Melatonin level for non-dipper ( 22.45 ± 2.48 pg/mL) were similar to dipper (20.5±2.4 pg/mL) which is not significant (P value 0.1) , while Night time Plasma Melatonin of non-dipper (36.76 ± 1.27 ) were reduced when compared to control (75.26 ± 2.99 pg/mL) and to dipper group (75.26 ± 1.8 pg/mL ) which was highly significant (p <0.0001 , p <0.0001) respectively . Conclusion: Night time Plasma Melatonin level reduced in Primigravid Women with preeclampsia that did not show nocturnal dipping in blood pressure.